Magnetic field regulated, controlled hyperthermia with LixFe3-xO4 (0.06 ≤ x ≤ 0.3) nanoparticles. Issue 9 (15th June 2019) - Srivastava, M.; Alla, S.K.; Meena, Sher Singh; Gupta, Nidhi; Mandal, R.K.; Prasad, N.K.
Abstract: The single phase Lix Fe3-x O4 (0.06 ≤ x ≤ 0.3) nanoparticles were synthesized using microwave refluxing technique and found to be spherical with the size in the range of ∼ 3–22 nm. The structure and the size were confirmed by X-ray diffraction patterns and transmission electron microscopy. X-ray photoelectron spectroscopy data of Li0.3 Fe2.7 O4 sample indicate the oxidation states for Li-ions (+1) and Fe-ions (+2 and + 3). The sample Li0.06 Fe2.94 O4 had superior magnetization value (∼54.1 Am 2 /kg) and it diminished with increasing Li content. The low coercivity values and the presence of a doublet in Mössbauer spectra advise the presence of both ferrimagnetic and superparamagnetic component. The ferrofluids of these samples show magnetic field dependent stabilization of temperature near 42 °C at the time of magnetic hyperthermia experiments. The specific absorption rate value (up to 100 W/g) found to be comparable with the literature values.